1996
DOI: 10.1021/jm950543x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Selective and Partial Agonists of 5-HT3Receptors. Part 1. Synthesis and Biological Evaluation of Piperazinopyrrolothienopyrazines

Abstract: A series of piperazinopyrrolo[1,2-a]thieno[3,2-e]- and -[2,3-e]pyrazine derivatives were prepared and evaluated in order to determine the necessary requirements for high affinity on the 5-HT3 receptors and high selectivity versus other 5-HT receptor subtypes. Various substitutions on the piperazine and the thiophene ring of the pyrrolothienopyrazine moieties were systematically explored as well as replacement of the piperazine by other cyclic amines. The best compounds are in the nanomolar range of affinity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…[13,14] Amine 18 was then alkylated with iodoethane to provide 5-diethylamine 23 or reacted with 2,5-dimethoxytetrahydrofuran to give pyrrole 28 in excellent yield (Scheme 4). [15] Azide 26 was also converted to 1,2,3-triazole analogue 32 by a [2+3] Huisgen cycloaddition with (trimethylsilyl)-acetylene. [16] Without solvent or catalyst, this reaction proceeded in a very efficient way and gave, after removal of the trimethylsilyl group with HF·Et 3 N, free 1,2,3-triazole derivative 33.…”
Section: Chemistrymentioning
confidence: 99%
“…[13,14] Amine 18 was then alkylated with iodoethane to provide 5-diethylamine 23 or reacted with 2,5-dimethoxytetrahydrofuran to give pyrrole 28 in excellent yield (Scheme 4). [15] Azide 26 was also converted to 1,2,3-triazole analogue 32 by a [2+3] Huisgen cycloaddition with (trimethylsilyl)-acetylene. [16] Without solvent or catalyst, this reaction proceeded in a very efficient way and gave, after removal of the trimethylsilyl group with HF·Et 3 N, free 1,2,3-triazole derivative 33.…”
Section: Chemistrymentioning
confidence: 99%
“…Flash chromatography was performed using silica gel Merck 40-70 µm (230-400 mesh). Preparations of compounds 1 26 , 2 25 , 3a 27 , 3b 28 , 3c 28 and 3d 20 have been previously described. …”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22] We found that two of them (5-MeO-DPAC and S 20244) displayed significant affinity for 5-HT 7 R. Subsequently, we planned This lack of selectivity has led us to translate the knowledge acquired in the benzopyran series, to aminopyrrolothienopyrazine series, which has been described recently as being the possible support of new 5-HT ligands. 7 24 So, in this paper, we report the synthesis of a series of tricyclic aminopyrrolothienopyrazine 25 analogues of benzopyran having the structure key elements previously mentioned. …”
Section: Introductionmentioning
confidence: 99%
“…The present work reports on the synthesis of 2-amino-and 4-aminothieno [2,3-d]pyrimidine derivatives which can be regarded or might behave prospectively as analogues to 5-HT 3 receptor ligands [22]. These compounds possess the three key pharmacophoric elements (an aromatic moiety, a hydrogen-bond acceptor and a basic amino group) required for interaction with the 5-HT 3 receptor [23] and are structurally related to quipazine, a potent ligand for the 5-HT 3 receptor [24].…”
Section: Introductionmentioning
confidence: 99%